علم المناسبة في سورة المجادلة - حسين، أحمد رشيد; ناهي، هيفاء رزاق (جامعة بغداد - كلية التربية ابن رشد, 2014)
تناول هذا البحث علم المناسبة في سورة المجادلة، وقد قمنا ببيان علم المناسبة وهو علم اضطلع ببيان سر الترتيب والروابط بين الآيات والسور ضمن النظم المعجز. وجاء اختيار هذه السورة لما لها من أهمية موضوعية في الجانب الاجتماعي والبناء الأسري والتشريعي. وأثبت البحث أن المناسبة مصطلح من مصطلحات علوم القران يقوم على الترتيب والروابط بين الآيات السور ويتناول أوجه التناسب الصوتي واللفظي والمعنوي في البيان القرآني. وإن علم المناسبة ركن أساس في منهج التفسير وكلاهما يقف على مقاصد السور وأهدافها في تفسير كتاب الله الكريم وبها تثبت وحدة السور القرآنية والإعجاز القرآني. وبين البحث أن آيات سورة المجادلة مترابطة مع بعضها من أولها إلى أخرها مثلها كمثل جميع سور القرآن الكريم، وقد ارتبط أسمها بمضمونها وتناسبت فاتحتها مع خاتمتها وإن فاصلة كل أية من آياتها لها علاقة مع موضوع الآية. This research tackles Almunasaba the science of matching in Al-Muajdala Sura. We showed the meaning of the Science of Matching, which is the branch of science that shows the interpretation of the connections among the verses and suras within the system of inimitable. The choice of the subjectivity in the social and domestic and legislative. The research proves that the term is one of the Quranic sciences which arranges the verses and the sauras. It tackles the aspects of the vocal suitability of the semantic in the Quranic rhetoric. The Almunasaba is an important pillar in the curricle of the interpretation of the verse. Both try to the construct the Book of Allah in which the unity of the Quranic suras are proved and the miracles nature. The researcher shows that the sura of Almujadala is like other suras in the holy Quran has been linked to the content and the essence with the theme of the Sura.
Keywords: القرآن الكريم -- سورة المجادلة -- أسباب النزول -- علم المناسبة